2010
DOI: 10.1068/a4249
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variations in the Early Diffusion of Corporate Voluntary Standards: Comparing ISO 14001 and the Global Compact

Abstract: Despite their availability to firms across the world, uptake of global voluntary standards has proceeded unevenly across countries over time. In this article, we seek to provide new insights into how geography shapes these spatio-temporal variations, focusing on two leading examples of codified voluntarism: ISO14001 and the Global Compact (GC).Advancing on previous quantitative studies, which have analyzed domestic and nondomestic influences separately, we examine how the internal attributes of place "conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(70 citation statements)
references
References 61 publications
3
67
0
Order By: Relevance
“…Existing spatially disaggregated, large-N evidence for these dynamics is restricted to private environmental standards (Albuquerque et al 2007;Perkins and Neumayer 2010;Prakash and Potoski 2006). Our estimations extend these results, strongly indicating that trading-up also operates in the case of public environmental standards, too.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Existing spatially disaggregated, large-N evidence for these dynamics is restricted to private environmental standards (Albuquerque et al 2007;Perkins and Neumayer 2010;Prakash and Potoski 2006). Our estimations extend these results, strongly indicating that trading-up also operates in the case of public environmental standards, too.…”
Section: Discussionsupporting
confidence: 77%
“…3 A large number of studies have shown that exports to, and inward investment from, countries which have a higher number of adopters of a particular code, e.g. ISO14001, increases the domestic adoption of the same code (Albuquerque et al 2007;Corbett and Kirsch 2001;Neumayer and Perkins 2004;Perkins and Neumayer 2010;Prakash and Potoski 2007 4 This demand for regulatory tightening was fuelled by growing public and political concern in Germany about the effects of 'acid rain' (Hagner 2000). Yet, government support for more stringent EU-wide standards was considerably strengthened by the fact that German vehicle manufacturers were major exporters to the higher-regulating US market, and therefore already producing vehicles capable of complying with more stringent standards (Boehmer-Christiansen and Weidner 1995;Vogel 1997).…”
Section: Previous Studies and Their Shortcomingsmentioning
confidence: 99%
“…In the following, this distinction will be maintained although it should be noted that internal and external factors are likely to interact (Perkins and Neumayer, 2010).…”
Section: Drivers Of Standards Adoptionmentioning
confidence: 99%
“…However, several evidences indicated that there is a positive relationship between degree of wealth and CSR reporting. For example, CSR certification like ISO 14001 in other economies are more likely to diffuse into a wealthier economy since there is a link between a country's level of economic development and the development of CSR performance [4][5]. It makes sense that higher levels of wealth per capita may provide more resources for the social and environmental initiatives.…”
Section: Csr Disclosure Varies For Each Regionmentioning
confidence: 99%